Value-based HR practices, i-deals and clinical error control with CSR as a moderator. Issue 4 (8th May 2017) - Luu, Tuan; Rowley, Chris; Siengthai, Sununta; Thanh Thao, Vo
Abstract : Purpose: Notwithstanding the rising magnitude of system factors in patient safety improvement, "human factors" such as idiosyncratic deals (i-deals) which also contribute to the adjustment of system deficiencies should not be neglected. The purpose of this paper is to investigate the role of value-based HR practices in catalyzing i-deals, which then influence clinical error control. The research further examines the moderating role of corporate social responsibility (CSR) on the effect of value-based HR practices on i-deals. Design/methodology/approach: The data were collected from middle-level clinicians from hospitals in the Vietnam context. Findings: The research results confirmed the effect chain from value-based HR practices through i-deals to clinical error control with CSR as a moderator. Originality/value: The HRM literature is expanded through enlisting i-deals and clinical error control as the outcomes of HR practices.